Exploring Digital Knowledge in a Rural East Java Community - Sari, Faizah; Tauryawati, Mey Lista; Sampe, Maria Zefanya (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
This paper presents an initiative aimed at introducing digital skills to a rural community in East Java, Indonesia. A training workshop on the use of electronic surveys was conducted through a classroom-style presentation. The session included a simple step-by-step tutorial, hands-on practice using a smartphone-based electronic survey form, and a demonstration of how the survey results could be visualized. Thirty adult participants, both men and women, from the village of Karangpakis, Kabuh Regency, East Java, took part in the workshop. The findings indicate that the community service activity highlighted both challenges and opportunities for digital empowerment, which are analyzed in three key areas: (1) the delivery of an accessible workshop that enabled participants to practice using an online survey application; (2) the significance of introducing technology to enhance communication regarding village welfare; and (3) the advancement of participants’ digital literacy through exposure to the practical benefits of the survey results. The paper concludes by discussing implications for sustainable engagement and directions for future research.